Congruences involving generalized Frobenius partitions - James Sellers (International Journal of Mathematics and Mathematical Sciences)
The goal of this paper is to discuss congruences involving the function cϕm¯(n), which denotes the number of generalized Frobenius partitions of n with m colors whose order is m under cyclic permutation of the m colors.